Duties of the buyer under the sale of goods in Shariʿah and International Trade Law - Mazin Abdulhameed Hassan,; Ahmad Azam Othman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The sale of goods constitutes one of the most prevalent forms of commercial transactions globally, undertaken by individuals and businesses alike to satisfy their diverse and continual needs. As a result, buyers are subject to specific obligations towards sellers, which are governed by applicable legal frameworks that differ across jurisdictions. This paper aims to critically examine the duties of buyers under both Shariʿah and international trade law, focusing on both primary and secondary obligations, and offering a comparative analysis of the two legal systems. This research adopts a doctrinal legal methodology alongside Islamic jurisprudential analysis, drawing from authoritative sources in both Shariʿah and international trade law. The findings reveal substantial parallels alongside notable divergences between the two frameworks in relation to the buyer’s obligations. Regarding primary obligations, both legal systems impose the duty to pay the agreed price in accordance with the terms of the contract, the duty to undertake necessary actions to facilitate such payment, and the duty to accept delivery of the goods. With respect to secondary obligations, the analysis identifies both convergence and divergence. Areas of convergence include the duty to notify the seller of contract rescission and the duty to preserve the goods. However, key differences emerge: under Shariʿah, unlike international trade law, the buyer is obliged to notify the seller of non-conformity only when intending to rescind the contract, and this duty is not constrained by a specific timeframe nor by any formal requirement to identify the defect in detail. Moreover, Shariʿah does not impose a post-contractual obligation on the buyer to specify the form, measurements, or characteristics of the goods, as such specifications are expected to be addressed prior to contract formation. Nevertheless, there exists significant potential for harmonizing the regulation of sale of goods transactions under Shariʿah and international trade law, thereby facilitating cross-jurisdictional legal coherence and commercial predictability.